Peningkatan Hasil Belajar Pendidikan Pancasila Peserta Didik Menggunakan Model Problem Based Learning (PBL) di Kelas IV SDN 08 Baringin Kabupaten Agam - Ramadhan, Putri; Fitria, Yanti (TSAQOFAH, 2026)
The low learning outcomes in Pancasila Education among Grade IV students at SDN 08 Baringin indicate the need to implement a more innovative, enjoyable, and student-centered learning model. This study aims to describe the improvement of students’ learning outcomes in Pancasila Education through the implementation of the Problem Based Learning model. This study used Classroom Action Research (CAR) with qualitative and quantitative approaches, which was conducted in two cycles through the stages of planning, implementation, observation, and reflection. The subjects of the study were the teacher and 22 Grade IV students of SDN 08 Baringin, Agam Regency. The research data were obtained from observations of teaching modules, the implementation of learning in terms of teacher and student aspects, and learning outcomes. Data collection techniques used tests and non-tests. The results show an improvement from Cycle I to Cycle II. The average assessment of the teaching module increased from 85.4% with a good qualification (B) to 92% with a very good qualification (A). The implementation of learning in the teacher aspect increased from 76.78% with a good qualification (C) to 92.86% with a very good qualification (A), while the student aspect increased from 85.68% with a good qualification (B) to 92.42% with a very good qualification (A). Students’ learning outcomes also increased from an average score of 77.02 with a sufficient qualification (C) in Cycle I to 92 with a very good qualification (A) in Cycle II. The conclusion of the study emphasizes that the implementation of the Problem Based Learning model can improve Pancasila Education learning outcomes among Grade IV students. The implications of this study indicate the importance of using problem-based learning models to encourage students’ activeness, engagement, and learning achievement in elementary schools.